2014
DOI: 10.1051/0004-6361/201322916
|View full text |Cite
|
Sign up to set email alerts
|

SimultaneousXMM-Newtonand HST-COS observation of 1H 0419–577

Abstract: In this paper, we present the longest exposed (97 ks) XMM-Newton EPIC-pn spectrum ever obtained for the Seyfert 1.5 galaxy 1H 0419-577. With the aim of explaining the broadband emission of this source, we took advantage of the simultaneous coverage in the optical/UV that was provided in the present case by the XMM-Newton Optical Monitor and by a HST-COS observation. Archival FUSE flux measurements in the far-ultraviolet were also used for the present analysis. We successfully modeled the X-ray spectrum and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 72 publications
(79 reference statements)
1
24
0
Order By: Relevance
“…Parameters obtained when fitting spectra with ionized-reflection models are often extreme. A maximally rotating supermassive black hole and a very steep emissivity are required in most cases Crummy et al 2006), as well as fine-tuning of the ionization of the disk (Done & Nayakshin 2007). These parameters, which are similar to those obtained when modeling the broad component of the Fe Kα line , show that in this scenario most of the reprocessed radiation is produced very close to the event horizon.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Parameters obtained when fitting spectra with ionized-reflection models are often extreme. A maximally rotating supermassive black hole and a very steep emissivity are required in most cases Crummy et al 2006), as well as fine-tuning of the ionization of the disk (Done & Nayakshin 2007). These parameters, which are similar to those obtained when modeling the broad component of the Fe Kα line , show that in this scenario most of the reprocessed radiation is produced very close to the event horizon.…”
Section: Introductionsupporting
confidence: 63%
“…The density structure assumed in a hydrostatic α disk (Shakura & Sunyaev 1973) is not always appropriate. In particular, it has been shown that the accretion disk cannot be in hydrostatic equilibrium if the soft excess is made via reflection (Done & Nayakshin 2007). In the relxilllp_ion model, the gas in the atmosphere of the accretion disk is assumed to be at a constant density .…”
Section: R Vs Q In Simulations Of Ionized Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implied strong X-ray illumination should also give rise to reprocessed emission in the optical/UV bands. The UV/optical emission of this AGN are found variable (see e.g., Di Gesu et al 2014;Pounds et al 2004b) and their detailed relationship with the X-ray emission is explorable.…”
Section: Introductionmentioning
confidence: 99%
“…By studying the correlations between the Suzaku light curves in different bands, Noda et al (2013) were able to extract the stable soft-excess component (Singh et al 1985) that may dominate the continuum emission at soft energies (i.e., below 2.0 keV). According to these authors, the most likely origin for the soft-excess in this source is thermal Comptonization of the disk photons in a warm plasma (see, e.g., Noda et al 2011;Done et al 2012;Jin et al 2012;Petrucci et al 2013;Di Gesu et al 2014;Giustini et al 2015;Boissay et al 2016). It was found, however, that the soft-excess underlies a heavy soft X-ray absorption.…”
Section: Introductionmentioning
confidence: 99%